Sulfur stoichiometry driven chalcopyrite and pyrite structure of spray pyrolyzed Cu-alloyed FeS2 thin films. (December 2015) - Rana, Tanka Raj; Khadka, Dhruba B.; Kim, JunHo
Abstract: We report on fabrication of Cu x Fe1− x S2 (CFS) thin films using chemical spray pyrolysis followed by post-sulfurization. Post-sulfurized CFS films were grown with compact and good crystalline texture. The sulfur stoichiometry in CFS films was found to be crucial for determination of its crystal structure. The sulfur deficient CFS films were driven to chalcopyrite CFS (CH-CFS) structure whereas the sulfur cured CFS films were grown with Cu-incorporated pyrite CFS (P-CFS) structure which was confirmed by X-ray diffraction and Raman spectroscopy analysis along with UV–vis spectroscopy measurement. Electrical characterizations of both types of CFS films revealed p-type conductivity with carrier concentration in the range of 10 18 –10 20 cm −3 and mobility of 0.5–9 cm 2 V −1 s −1 . The band gaps of CFS films of CH-CFS structure (0.885–0.949 eV) were found to be less than that of P-CFS structure (0.966–1.156 eV), which indicates its potential application for thermoelectric and photovoltaic devices.